Hydration and health at ages 40–70 years in Salzburg Austria is associated with a median total water intake over 40 mL/kg including at least 1 L/d plain drinking water - Stookey, Jodi D.; Langthaler, Patrick B.; Felder, Thomas K.; Frey, Vanessa N.; van der Zee-Neuen, Antje; Schindler, Karin; Kedenko, Ludmilla; Iglseder, Bernhard; Trinka, Eugen; Lang, Florian; Häussinger, Dieter; Ritter, Markus; et al. (Frontiers in Public Health, 2025)
IntroductionTo address longstanding questions about how much plain water to drink for hydration and long-term health, this study described the plain water intake (PWI) of people without chronic health conditions (CHC), at ages 40–70 years, who met hydration criteria (Healthy+Hydrated).MethodsCommunity-dwelling participants in the population-based Paracelsus 10,000 study in Salzburg, Austria (n = 5,817, 40–70 years), completed the EPIC diet questionnaire, blood and urine collection, and clinical assessment for CHC, including obesity, diabetes, hypertension, metabolic syndrome, cancer, liver, digestive tract, lung, kidney, cardiovascular and cerebrovascular disorders. Participants with serum tonicity 285–294 mOsmol/L and urine specific gravity (USPG) < 1.013 were classified as Hydrated. Cross-sectional analyses described the PWI of Healthy+Hydrated adults, compared to groups not meeting criteria for hydration (Healthy+Not Hydrated), health (CHC+Hydrated), or both (CHC+Not Hydrated), and relative to body weight and total water intake (TWI).ResultsFor Healthy+Hydrated women, the median PWI and TWI were 1.5 L/d (22 mL/kg) and 2.9 L/d (45 mL/kg), respectively. For Healthy+Hydrated men, the median PWI and TWI were 1.3 L/d (17 mL/kg) and 3.0 L/d (40 mL/kg). None of the Healthy+Hydrated reported zero PWI. In gender-specific Poisson models, the Healthy+Hydrated group had significantly lower relative risk of PWI < 20 mL/kg AND TWI < 45 mL/kg than each of the CHC+Hydrated, Healthy+Not Hydrated, and CHC+Not Hydrated groups. For Healthy+Hydrated participants with >60% of TWI from PWI, PWI ranged between 20 and 45 mL/kg/d.ConclusionIn the Paracelsus 10,000 study population, hydration and health at ages 40–70 years was associated with a median PWI of at least 1 L/d.